The Effect of the Use of Type of Wood on the Appearance and Flavor of Smoked Skipjack - Rinto M. Nur; Iswandi Wahab; Juwita Kore; Ningsi Saibi (East Asian Journal of Multidisciplinary Research, 2023)
This study aimed to analyze the influence of different types of wood on the appearance and taste of smoked fish. This study used four types of firewood: coconut tranks, driftwood, coconut husks, and sawdust. Fish that have been smoked are then carried out an organoleptic assessment of appearance and taste by 30 consumer panelists. The results showed that using different firewood types affects the appearance and taste of smoked skipjack fish. Smoking using coconut trunk wood provides an organoleptic value of appearance (8.07) and taste (8.40), according to Indonesian National Standard (>7). In contrast, the other three types of the wood show an organoleptic value of appearance and tasteless than 7.